USE HYPOBARIC HYPEROXYGENATION IN TREATMENT OF ACUTE PURULENT PYELONEPHRITIS PILOT ASSESSMENT MORPHOLOGICAL PARAMETERS - J. M. Goncharova; V. V. Kuzmenko; A. V. Kuzmenko (Вестник урологии, 2014)
Results of treatment of 60 mongrel dogs using hypobaric superoxygenation modes 500, 1500 and 3000 meters above sea level and the simultaneous flow of humidified oxygen 70-80%. The efficiency of hypobaric superoxygenation mode of 1500 meters above sea level, consisting in the regression of the inflammatory process.